IDENTIFICATION OF UNBALANCED FORCES AND FOUNDATION PARAMETERS OF ROTATING MACHINES FROM VIBRATION MEASUREMENTS - Nalitolela, N. G. (Tanzania Journal of Engineering and Technology, 2018)
A technique is described to use measured vibration data of a rotating machine and its foundation to identify unbalanced forces, stiffness and damping parameters of the mountings, and the parameters of the foundation. It is based on an idealisation treating the rotor, the machine structure and the foundation as rigid masses supported by springs and dampers. Operational vibration data of the machine and its foundation before and after the rotating unbalanced forces are perturbed by adding unbalanced mass to the rotor are used in the identification procedure. Once the parameters are identified, dynamic forces transmitted to the foundation can be estimated. The technique is demonstrated using simulated example for a machine with a two bearings rotor.